Geographical indications of vegetables in India - Hiremath, Varun M; Raghavendra, H R; Tejukumar, B K; Udaya, T V (Indian Horticulture, 2020)
Protection of intellectual property rights through GI is an important instrument in promotion of cultivation and conservation of vegetable varieties. Various institutions, state departments, govt. agencies and NGO’s are involved in ensuring legal protection for Indian GI products. Granting GI tags to popular vegetable types will help to promote local people, rural communities/enterprises to ensure wider access to markets. Govt. of India recently proposed ‘One Product One District’ (OPOD) approach, an action plan for promoting horticulture crops. It involves linking the said initiative with registration of GI products. It was already implemented in Japan and Thailand and has contributed to the rural development in both the countries. This approach would recognize to local products, traditional knowledge, bring down unemployment rate and more income for the rural community. GI products of vegetables have huge economic potential to reach global market and earn higher foreign exchange thereby enhance national income of country. Effective post-GI mechanism may be implemented to avoid unethical marketing practices and intervention of middlemen in domestic markets.